Effect of PRECEDE–PROCEED Model on the Decision-Making of Implant Contraceptive Method among Women of Reproductive Age - Enny Suramto; Setyo Sri Rahardjo; Revi Gama Hatta Novika; Ika Sumiyarsi Sukamto; Erindra Budi Cahyanto (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Implant contraception is a highly effective long-acting contraceptive method, but its use among women of reproductive age remains suboptimal. Decisions to use implant contraception are influenced by demographic characteristics, predisposing factors, enabling factors, and reinforcing factors. This study aimed to analyze the direct and indirect effects of PRECEDE–PROCEED Model indicators on decision-making regarding implant contraceptive use among women of reproductive age in the working area of Miri Public Health Center, Sragen Regency. Subjects and Method: A cross-sectional study was conducted among 422 women of reproductive age in the working area of Miri Public Health Center, Sragen Regency, Central Java, Indonesia. Respondents were selected using fixed control sampling. The dependent variable was implant contraceptive use. Independent variables included education, age, occupation, income, knowledge, attitude, enabling factors, family support, social support, and community support. Data were collected using a structured questionnaire and analyzed using the Chi-square test and path analysis with Generalized Structural Equation Modeling. Results: Implant contraceptive use was directly increased by age (b=2.56; 95% CI=1.82 to 3.31; p<0.001), family support (b=0.94; 95% CI=0.22 to 1.65; p=0.010), social support (b=2.75; 95% CI= 1.78 to 3.72; p<0.001), and positive attitude (b=2.57; 95% CI=1.82 to 3.33; p<0.001). Conversely, education (b=-1.09; 95% CI=-1.80 to -0.38; p=0.003) and occupation (b=-1.00; 95% CI= -1.73 to -0.28; p=0.006) reduced implant contraceptive use. Income and enabling factors showed no significant direct effects. Attitude was positively influenced by age (b= 1.17; p<0.001), knowledge (b= 0.82; p= 0.037), and family support (b= 1.38; p<0.001), while social and community support had no significant effects. Conclusion: Implant contraceptive use was influenced by age, education, occupation, family support, social support, and attitude. Attitude acted as an important mediator linking age, knowledge, and family support to implant contraceptive use.